International academic mobility, agency, and LGBTQ+ rights: a review of policy responses to internationally mobile LGBTQ+ staff/students at UK HE institutions with recommendations for a global audience. Issue 1 (2nd January 2022) - Hamilton, Frances; Giles, Cameron
ABSTRACT: Globalisation is a major driving factor in the Higher Education sector, which has resulted in significant developments relating to international academic mobility. This includes the establishment of international campuses, increasingly global facing research and extensive student international exchange schemes. We explore the advice given to LGBTQ+ staff and students in UK Higher Education Institutions ('HEIs') who engage in international mobility of this kind. Analysing data collected through Freedom of Information requests, we demonstrate that the advice given is overwhelmingly heteronormative, ignoring the potential challenges that LGBTQ+ travellers might fact and underestimating the impact of the disparate global landscape of LGBTQ+ rights. Drawing on agency literature, we argue that HEIs should develop detailed and informed policy which gives LGBTQ+ travellers greater agency during the travel process. We suggest that the lessons that can be learned from the UK context can be applied internationally by HEIs adapting to and developing in the increasingly globalised HE landscape.